Benefit–risk assessment of pitavastatin for the treatment of hypercholesterolemia in older patients - Chamberlin KW (Dove Medical Press, 2015)
Kevin W Chamberlin,1,2 William L Baker1,2 1School of Pharmacy, the University of Connecticut, Storrs, CT, USA; 2School of Medicine, the University of Connecticut, Farmington, CT, USA Abstract: With the practice-shifting changes made with the most recent guidelines for treating blood cholesterol, more older patients may be prescribed statin therapy. Therefore, it is imperative that practitioners have not only a working knowledge of information related to statins, but more specifically to their efficacy and safety in elderly populations. Pitavastatin is the most recent statin to receive regulatory approval. It is indicated for the treatment of primary hyperlipidemia or mixed dyslipidemia as an adjunctive therapy to diet. The overall body of evidence for the efficacy and safety of pitavastatin in elderly patients is small. The available data suggest that the ability of pitavastatin to lower low-density lipoprotein cholesterol in elderly patients is at least similar, and may be greater than that seen in comparatively younger cohorts. Taken together, the limited available data suggest that pitavastatin is effective at improving lipid parameters in elderly patients with a similar safety profile to other agents in the class. Until data become available distinguishing pitavastatin from the other available options, its ultimate role in the hyperlipidemia treatment armamentarium remains unclear. Keywords: pitavastatin, hypercholesterolemia, elderly